Unlocking full-domain flood inundation prediction from sparse point supervision in deep-learning models - Jiqiang Xie; Yuhang Zhang; Heng Lyu; Quan J. Wang; Shengnan Fu; Chi Zhang (Water Research, 2027)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Tracing microplastics uptake and translocation in plants using aggregation-induced emission materials - Yang Liu; Siqi Yang; Xia Wang; Wei Du; Nan Fu; Penglin Li; Heng Wei; Fen Zhao; Zijie Qiu; Hao Qiu; Yanxu Zhang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Carboxymethyl glucuronoxylan /PVA/nano ZnO composite films for blueberry preservation: The effects of nano-ZnO on the packaging properties of the composite films - Xinran Fu; Zhenhua Hu; Zhouyang Xiang; Xiaoran Zhang; Heng Zhang; Xin Tong; Hansheng Gong (Food Chemistry, 2026)

Selective cleavage of Cβ-O-containing Cα-Cβ bond on Cu-Ni3S2 for electrocatalytic glycerol oxidation to formic acid - Ruirui Xu; Xinti Yu; Ce Fu; Lina Li; Zhangxing Chen; Heng Zhao (Chemical Engineering Journal, 2026)

Optimization and Analysis of a Long-Arm Intelligent Marine Sampling Platform - Heng Zhou; Lejingyi Zhou; Haibo Wu; Minghao Xu; Lindan Zhang; Jia Guo; Wei Fu; Hengchi Zheng; Tian Ni (Journal of Marine Science and Engineering, 2026)
As the core equipment for in situ deep-sea scientific research, the design quality and operational performance of the sampling platform determine the efficiency of deep-sea operations, including long-term continuous observation, high-quality sampling and preservation, and in situ experimental studies. To address technical bottlenecks commonly observed in conventional platforms, including track sinkage, excessive motion drag, and low propulsion efficiency, this study proposes the design and development of a novel sampling platform with tracked-propeller dual-mode propulsion, deployable from either a surface vessel or a large manned submersible, capable of high-throughput, multi-sequence fidelity water sampling, in situ sediment incubation, and seabed mudstone sampling in deep sea. Through hydrodynamic performance analysis and design optimization, both lightweight design and drag reduction were achieved. Furthermore, load verification of the main frame under multiple operating conditions was conducted; results demonstrate that the structure meets strength and stiffness requirements and ensures reliability in typical service environments. This study provides a theoretical basis and technical reference for the development of similar deep-sea sampling platforms and holds substantial engineering application value.

Control of zeolite local microenvironment by organofluorination engineering toward efficient c-C4F8/C3F8 separation - Rui Sun; Zicheng Wan; Yaqi Wu; Yaohan Fu; Yang Zhang; Chenyang Yang; Heng Zhao; Ziqi Tian; Liang Chen (Chemical Engineering Journal, 2026)

Rapid Identification of Flood Inundation Areas and Dominant Drivers in Compound Floods using Explainable Machine Learning - Jiqiang Xie; Bing Yu; Heng Lyu; Shengnan Fu; Chen Yang; Chi Zhang (Water Resources Management, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Metamorphism and chronology of Neoproterozoic granulite facies metasedimentary rock in northwestern Yangtze Block and its tectonic implications - Linfeng Feng; Haozheng Wang; Byung Choon Lee; Jinghao Fu; Yi Zhang; Heng Liu; Meimei Han; Bo Hu; Xiahong Cui; Mingguo Zhai (International Geology Review, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

The Coupling Mechanisms of Alkalinity–Salinity–Soil Inorganic Carbon in Saline–Alkali Soils along the Yellow River - Hongfang Li; Hu Liu; Fu Heng; Hui Zhou; Qi Wang; Jian Wang (Journal of Soil Science and Plant Nutrition, 2026)

Space weathering on the lunar nearside and farside revealed by iron and potassium isotopes - Heng-Ci Tian; Wei Yang; Xinmiao Zhao; Jun Du; Liyu Shan; Wen-Jun Li; Jing Wang; Xuhang Zhang; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Revealing the Key Role of Chelates in Enhancing Fertilizer Performance: A Review - Kejian Fu; Yucui Sun; Yingying Li; Darun Yang; Heng Li (Journal of Soil Science and Plant Nutrition, 2026)

Electrochemical nitrate reduction for sustainable nitrogen and resource cycles: Progress and prospects - Zhenzhou Li; Jiawei Liang; Yifan Dai; Shihao Fu; Jialong Chen; Yunyang Sun; Jinlong Wang; Han Zhang; Daliang Xu; Jiaxuan Yang; Heng Liang (Critical Reviews in Environmental Science and Technology, 2026)

MT-WavYOLO: bridging multi-task learning and 3D frustum fusion for non-destructive robotic harvesting of occluded orchard fruits - Heng Fu; Tao Li; Qingchun Feng; Liping Chen (Computers and Electronics in Agriculture, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Retention of fracturing fluid in shale oil formations based on 1D- and 2D-NMR: Implications to shale oil production - Xiao Yan; Zhenkai Huang; Zengmin Lun; Jiangna Fu; Tao Zhang; Chunpeng Zhao; Heng Wang; Yibing Xie; Chunyan Fan; Dengfeng Zhang; Jie Zou (Fuel, 2026)

Interfacial proton transfer in MOF-functionalized aerogel enabling for selective heavy metal adsorption - Jun-Heng Fu; Baihang Cai; Yeshuang Zhong; Xinru Gong; Shuangfeng Fang; Fei Wang; Yufeng Yan; Rui Dai; Puyuan Liu; Jianye Gao; Ruihan Wang; Ying Cao; et al. (Desalination, 2026)

Regulation of soil physical environment and erosion characteristics of farmland by amendments in the black soil region of Northeast China - Xu Leng; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Mo Li; Dong Liu; Zhaoqiang Zhou; Di Wu (Soil and Tillage Research, 2026)

The Hongjianbingshan W–Li–(Be) deposit in the Beishan Orogenic Belt is not related to carboniferous magmatic–hydrothermal events: Insights from multi-mineral U-Pb and zinnwaldite Rb-Sr geochronology - Yong Yin; Heng-Feng Zhang; Zhuang Duan; Bing-Fei Yu; Heng Luo; Yan-Gang Fu; David R. Lentz; Tao Luo; Ke-Yu Ren; Zhe Ren; Hao Hu (Journal of Geochemical Exploration, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Insights into the enhanced flux and robust desalination of hydrogel composite Janus membrane in membrane distillation: overlooked interfacial compatibility - Shu Jiang; Anqi Luo; Shilei Fu; Yanrui Wang; Kexin Hou; Jun Ma; Longfeng Hu; Nuo Cheng; Xiaobin Tang; Heng Liang (Chemical Engineering Journal, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Metabolic fate of polyphenols in LAB-fermented kiwifruit juice: A comparative study of single and mixed cultures with targeted metabolomics and enzymatic evidence - Heng Liu; Weichong Fu; Xinyue Lian; Chengwei Pu; Xinxin Wu; Jingming Li (Food Chemistry, 2025)

Light-activated dialdehyde cellulose nanocrystals (DACNC)-erythrosine generates ROS for Vibrio inactivation in whiteleg shrimp - Dewi Nur’aeni Setyowati; Shao-Chen Lu; Yong-Ching Heng; Jia-Wei Zhou; Yi-Min Chen; Shih-Chen Shi; Fu-I Lu (Fish & Shellfish Immunology, 2025)

Prediction and interpretability analysis of hydraulic conductivity for polymer-amended soil-bentonite cutoff wall backfills using machine learning methods - Heng Zhuang; Xian-Lei Fu; Hao Ni; Yan-Jun Du (Environmental Research, 2025)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

Activating graphitic carbon via a core/shell WO3/carbon architecture for electrocatalytic deactivation of dilute antibiotics - Wenyang Fu; Yanjun Yin; Jiahong Zou; Chunyang Dan; Shenbin Zheng; Huimin Sui; Yinan Liu; Yan Zou; Heng Shi; Guangming Jiang (Chemical Engineering Journal, 2025)

Low-molecular-weight dextran sulfate sodium as novel heparanase inhibitor preventing breast cancer metastasis in mice by inhibiting migration and angiogenesis - Yidian Mo; Guohao Song; Linbo Fu; Yuchao Wang; Tongtong Geng; Ao Sun; Baodi Gou; Xiangbao Meng; Liangren Zhang; Heng Wang; Zhongjun Li; Zhongtang Li (Carbohydrate Polymers, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Characterization of 4-coumarate CoA ligase (4CL) gene family and functional study of Sm4CL2/3/7/9 in Salvia miltiorrhiza - Fan Fu; Huiting Qin; Yujie Xin; Qianmo Li; Heng Kang; Limin Han; Wenping Hua; Xiaoyan Cao (Functional & Integrative Genomics, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

High-order CBF based event-triggered control for trajectory tracking of USVs with input saturation and unknown disturbances - Heng Zhang; Yujie Xu; Mingyu Fu; Zhipeng Fan (Ocean Engineering, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Sequence of middle-lower Ordovician in Shunbei area of Tarim Basin, China, and its geological significance - Rui Xiong; Heng Fu; Yong Li; Caizhu Xie; Ronggang Wang; Shaoze Zhao; Chuan Xu; Chongyang Xiao (Carbonates and Evaporites, 2025)

Deposition and release of clay colloids on alumina and natural organic matter surfaces via heterogeneous pathways - Yuanqi Fu; Heng Wang; Zhenyu Yang; Liangke Liu; Xiaohu Jin; Yajing Huang; Xiaoyao Wang; Xiaoyun Yi; Zhi Dang (Applied Clay Science, 2025)

Directly determine the electron-neutrino mass with sub-eV sensitivity by the decay of 159 Dy - Ying Fu; Yuekun Heng (Science Bulletin, 2025)

Geraniol combined nerolidol inhibited soft rot caused by Pectobacteriumn aroidearum in red pickled pepper - Liu Heng; Hu Jingjing; Liu Hu; Zhang Zhanquan; Tian Subo; Chen Qingmin; Jiao Wenxiao; Fu Maorun (Postharvest Biology and Technology, 2025)

Novel one-step solid-state synthesis of 2D Ni/C for efficient electro/photo-catalytic hydrogen evolution - Heng Ke; Yaya Xie; Yi Luo; Yinhong Gao; Lan Yin; Jun Fu; Liangzhe Chen (Fuel, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Mechanisms of endothelial senescence and vascular aging - Qiao Li; Zonghao Qian; Yuzhen Huang; Xiao Yang; Jiankun Yang; Nanyin Xiao; Guangyu Liang; Heng Zhang; Yanguang Fu; Yan Lin; Cuntai Zhang; Anding Liu (Biogerontology, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Integration of moving bed biofilm reactor and gravity-driven membrane bioreactor for decentralized domestic wastewater treatment: Efficiency and mechanistic insights - Zixin Ma; Ziao Zhang; Shilei Fu; Linqiao Jiang; Yitong Sun; Yichun Zhu; Yanrui Wang; Wenjun Cheng; Xiaobin Ma; Heng Liang; Xiaobin Tang (Bioresource Technology, 2025)

Application of a superior magnetic hydroxy iron material for arsenic removal from soil - Liangke Liu; Heng Wang; Yuanqi Fu; Liyang Gao; Zhenyu Yang; Xiongkai Zheng; Yuekang Chen; Yajing Huang; Xiaoyao Wang; Xiaoyun Yi; Zhi Dang (Environmental Research, 2025)

The role of ATG7-mediated ferroptosis in formaldehyde-induced ovarian injury in rats - Kun Mao; Hao-zhe Yan; Jia-qi Yang; Zi-xin Yin; Xin-qi Gao; Hao-fu Liu; Heng Su; Yuan-yuan Geng; Pan Ge; Dang-xia Zhou (Reproductive Toxicology, 2025)

Ozone-mediated carboxylation: a strategy for enhanced organic matter removal via in-situ crystallization of hardness ion - Keqian Li; Yujia Han; Yi Chen; Zhihao Fu; Heng Quan; Yadong Wang; Yabo Shang; Juan Shi; Pengkang Jin; Xin Jin (Journal of Cleaner Production, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

Regulatory Roles of Exosomes in Aging and Aging-Related Diseases - Nanyin Xiao; Qiao Li; Guangyu Liang; Zonghao Qian; Yan Lin; Heng Zhang; Yangguang Fu; Xiao Yang; Cun-Tai Zhang; Jiankun Yang; Anding Liu (Biogerontology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Indirect Z-scheme MXene@g-C3N4/MIL-101(Fe) heterojunction for the enhanced visible-light-responsive enrofloxacin photodegradation - Zhi-Fu Lin; Tzu-Heng Wang; Prashanth Venkatesan; Ruey-An Doong (Chemical Engineering Journal, 2025)

Low-temperature oxidative pyrolysis characteristics of tobacco components - Zhongya Guo; Ke Zhang; Huanwei Li; Lili Fu; Qi Zhang; Ze Liu; Le Wang; Xueyi Qiao; Heng Guo; Ran Chen; Bing Wang; Bin Li (Biomass and Bioenergy, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Response of soil phosphorus components to black carbon in seasonally frozen areas: Insight into ecoenzymatic stoichiometry - Ping Xue; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Mo Li; Song Cui; Zhaoqiang Zhou; Qinglin Li (Applied Soil Ecology, 2025)

Regulation of terrestrial input and ocean processes on the occurrence and transport of traditional and emerging per- and polyfluoroalkyl substances in the inner shelf of the East China Sea - Jincai Zhu; Yao Fu; Heng Hu; Yisen Zhong; Xiao Ma; Yuanli Zhu; Feng Zhou; Yitao Pan; Yuxin Ma (Water Research, 2025)

Structural characteristics of areca nut seed neutral polysaccharide and its impact on gut microbiota from human feces - Mengfan Zhang; Haining Zhuang; Xiaowei Zhang; Xiaoyu Wang; Xia Fu; Sheng Chen; Lingyun Yao; Huatian Wang; Min Sun; Chuang Yu; Heng Yue; Tao Feng (Food Hydrocolloids, 2025)

Abundant surface adsorbed oxygen species originated from defect/vacancy sites during preferential CO oxidation - Yang Liu; Kunming Hou; Zhihua Guo; Yan Guo; Yue Jiang; Xinya Wu; Zewei Fu; Heng Zhang; Ping Li; Shanghong Zeng (Chemical Engineering Journal, 2025)

Novel magnetic adsorbents based on oyster and clam shells for the removal of cadmium in soil - Heng Wang; Yuanqi Fu; Kexin Guo; Xiaofei Li; Xiaohu Jin; Yajing Huang; Xiaoyao Wang; Guining Lu; Xiaoyun Yi; Zhi Dang (Science of The Total Environment, 2024)

Sedimentary antimony stable isotope record of anthropogenic contamination in a karst lake in southwestern China - Qianwen Deng; Xian Wu; Hui Zhang; Yunjie Wu; Kaihui Tang; Ye Sun; Guangyi Sun; Heng Yao; Jonas Olof Sommar; Xuewu Fu; Xinbin Feng (Science of The Total Environment, 2024)

Time-guided convolutional neural networks for spatiotemporal urban flood modelling - Ze Wang; Heng Lyu; Guangtao Fu; Chi Zhang (Journal of Hydrology, 2024)

Critical role of soil-applied molybdenum dioxide composite biochar material in enhancing Cr(VI) remediation process: The driver of Fe(III)/Fe(II) redox cycle - Mingxuan Liu; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Ping Xue; Xuechen Yang; Mo Li; Dong Liu (Journal of Environmental Management, 2024)

Effects of biochar and compost on the abundant and rare microbial communities assembly and multifunctionality in pesticide-contaminated soil under freeze‒thaw cycles - Guoxin Shi; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Qingshan Chen; Ping Xue (Environmental Pollution, 2024)

A flexible and superhydrophobic PVDF-HFP@PVA bilayer enables high-performance radiative cooling and thermal management - Jun-Heng Fu; Qigong Zhang; Minglei Yan; Wei Tang; Yun Zeng; Yuntao Cui; Mingkuan Zhang; Hongwei Deng; Hao Kang; Xinlong Sun; Liang Qiao; Hongzhang Wang; et al. (Chemical Engineering Journal, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Bioinspired carbon black deposited polyimide fabric for sustainable water energy harvesting - Jianhong Guo; Leyan Zhang; Chunhua Zhang; Dandan Zhong; Weihao Long; Jieyao Qin; Zhuan Fu; Sijie Zhou; Junyao Gong; Heng Pan; Hua Ji; Lixin Du; et al. (Chemical Engineering Journal, 2024)

A new species of Eirictis (Mammalia, Carnivora, Mustelidae) from Lower Pleistocene of Yuanmou Basin, Yunnan, China - Arya Farjand; Li-Ya Fu; Qi-Gao Jiangzuo; Zhi-Heng Liu; Jian Wang; Xin-Ying Zhou; Shun-Dong Bi; Li-Hua Wang (Palaeoworld, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Tracing the centennial variation of East Asian Summer Monsoon - Heng Fu; Feng Shi; Wei Liu; Huihong Xue; Wenmin Man; Juan Li; Zhengtang Guo (Global and Planetary Change, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Biocompatible porous material templated from gliadin particle and gellan gum co-stabilized wet foam - Fu-Zhen Zhou; Tao Yang; Huan Xiang; Long-Tao Zhang; Shu-Heng Wei; Jian-Hua Zhu; Xiao-Quan Yang; Shou-Wei Yin (Food Hydrocolloids, 2024)

A comprehensive study on seismic dynamic responses of stochastic structures using sparse grid-based polynomial chaos expansion - Heng Zhao; Yaqiong Zhang; Weidong Zhu; Chao Fu; Kuan Lu (Engineering Structures, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Hydraulic conductivity and microscopic properties of polyanionic cellulose and microscale zero-valent iron amended sand/bentonite backfills exposed to dichloromethane solution - Heng Zhuang; Guang-Yu Yang; Xian-Lei Fu; Zhe-Yuan Jiang; Yan-Jun Du (Science of The Total Environment, 2024)

Short-term effects of exposure to ambient PM2.5 and its components on hospital admissions for threatened and spontaneous abortions: A multicity case-crossover study in China - Heng He; Na Wan; Zhenzhen Li; Zihan Zhang; Zesen Gao; Qingdan Liu; Xiaolei Ma; Yuqing Zhang; Rongxiang Li; Xiuhong Fu; Weihong Qiu (Chemosphere, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Lithium and oxygen isotopic constraints on the source and evolution of ore-forming fluids: a case study from the Shuiyindong Carlin-type gold deposit, SW China - Ningning Hu; Ruizhong Hu; Heng Chen; Shanling Fu; Jiehua Yang; Lin Xu; Chongguang Luo (Mineralium Deposita, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Changes in Mental Health and EEG Biomarkers of Undergraduates Under Different Patterns of Mindfulness - Miaoling Luo; Quan Gan; Ziyang Huang; Yunxiong Jiang; Kebin Li; Minxiang Wu; Dongxiao Yang; Heng Shao; Yanmei Chen; Yu Fu; Zhuangfei Chen (Brain Topography, 2024)
The effects of short-term mindfulness are associated with the different patterns (autonomic, audio guided, or experienced and certified mindfulness instructor guided mindfulness). However, robust evidence for reported the impacts of different patterns of mindfulness on mental health and EEG biomarkers of undergraduates is currently lacking. Therefore, we aimed to test the hypotheses that mindfulness training for undergraduates would improve mental health, and increase alpha power over frontal region and theta power over midline region at the single electrode level. We also describe the distinction among frequency bands patterns in different sites of frontal and midline regions. 70 participants were enrolled and assigned to either 5-day mindfulness or a waiting list group. Subjective questionnaires measured mental health and other psychological indicators, and brain activity was recorded during various EEG tasks before and after the intervention. The 5-day mindfulness training improved trait mindfulness, especially observing (p = 0.001, d = 0.96) and nonreactivity (p = 0.03, d = 0.56), sleep quality (p = 0.001, d = 0.91), and social support (p = 0.001, d = 0.95) while not in affect. Meanwhile, the expected increase in the alpha power of frontal sites (p < 0.017, d > 0.84) at the single electrode level was confirmed by the current data rather than the theta. Interestingly, the alteration of low-beta power over the single electrode of the midline (p < 0.05, d > 0.71) was difference between groups. Short-term mindfulness improves practitioners’ mental health, and the potentially electrophysiological biomarkers of mindfulness on neuron oscillations were alpha activity over frontal sites and low-beta activity over midline sites.

Novel use of ferrous iron/peroxymonosulfate for high-performance seawater desalination pretreatment under harmful algal blooms - Boyan Xu; Xiaohui Lu; Yuyao Fu; Liyue Diao; Heng Liang; Sungwoo Bae; How Yong Ng; Jun Ma (Water Research, 2023)

Double redox-active polyimide-based covalent organic framework induced by lithium ion for boosting high-performance aqueous Zn2+ storage - Yafei An; Heng Zhang; Dongxiang Geng; Zhijian Fu; Ziming Liu; Jing He; Yue Zhao; Minjie Shi; Chao Yan (Chemical Engineering Journal, 2023)

CDKN2B-AS1 mediates proliferation and migration of vascular smooth muscle cells induced by insulin - Hao-jie Jin; Zi-heng Wu; Bao-fu Zhang; Jie Deng; Yin-dong Xu; Xin-yu Wang; Zheng-yang Song; Xin-wu Lu; Wan-tie Wang; Xiang-tao Zheng (Cell and Tissue Research, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

A review on polyhydroxyalkanoates production from various organic waste streams: Feedstocks, strains, and production strategy - Xuemei Fu; Heng Xu; Qi Zhang; Jiaxing Xi; Huihui Zhang; Mingxia Zheng; Beidou Xi; Li'an Hou (Resources, Conservation and Recycling, 2023)

Identification of pancreatic lipase inhibitors from Eucommia ulmoides tea by affinity-ultrafiltration combined UPLC-Orbitrap MS and in vitro validation - Han Huang; Ming-Hao Han; Qi Gu; Jian-Dong Wang; Heng Zhao; Bo-Wen Zhai; Si-Ming Nie; Zhi-Guo Liu; Yu-Jie Fu (Food Chemistry, 2023)

Risk assessment of geological disasters in Beichuan County after the Wenchuan earthquake based on ArcGIS - Fu-gang Xu; Yi-heng Ou; Feng Wang; Bo-wen Wei; Ruokun-Nie (Bulletin of Engineering Geology and the Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Late Mesoproterozoic to early Neoproterozoic metamorphic history of the North Wulan terrane, NW China: New constraints on the evolution of Rodinia - Jiahao He; Xiucai Li; Manlan Niu; Chris Yakymchuk; Chen Li; Zhen Yan; Changlei Fu; Zhe Heng (Journal of Asian Earth Sciences, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

miR-665 overexpression inhibits the apoptosis of luteal cells in small ruminants suppressing HPGDS - Heng Yang; Lin Fu; Licai Li; Dezhi Zhang; Qianyong Li; Peng Zhou (Theriogenology, 2023)

Antibiotic resistance genes in food production systems support One Health opinions - James M. Tiedje; Yuhao Fu; Zhi Mei; Andreas Schäffer; Qingyuan Dou; Wulf Amelung; Martin Elsner; Joseph Adu-Gyamfi; Lee Heng; Marko Virta; Xin Jiang; Hauke Smidt; et al. (Current Opinion in Environmental Science & Health, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

A novel SAR and optical image fusion algorithm based on an improved SPCNN and phase congruency information - Yukai Fu; Shuwen Yang; Yikun Li; Heng Yan; Yao Zheng (International Journal of Remote Sensing, 2023)

Integrated membrane electrochemical reactor-membrane distillation process for enhanced landfill leachate treatment - Zhongsen Yan; Zhengshi Zhu; Haiqing Chang; Gongduan Fan; Qiankun Wang; Xianzhi Fu; Fangshu Qu; Heng Liang (Water Research, 2023)

Clostridium butyricum-fermented Chinese herbal medicine enhances the immunity by modulating the intestinal microflora of largemouth bass (Micropterus salmoides) - Xiaolin Meng; Huimin Cai; Heng Li; Fu You; Aixia Jiang; Wenpan Hu; Keke Li; Xindang Zhang; Yanmin Zhang; Xulu Chang; Guokun Yang; Zhigang Zhou (Aquaculture, 2023)

Outstanding energy reduction of nitrogen recovery by biohythane concept introduction by 3D-weaved anode network in microbial electrolysis cell - Shuai Luo; Xianzheng Zhu; Boya Fu; Fubin Liu; Lequn Sun; Kai He; Heng Yang; Xiaoyuan Zhang; Xia Huang (Resources, Conservation and Recycling, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Mutation of rpoS is Beneficial for Suppressing Organic Acid Secretion During 1,3-Propandiol Biosynthesis in Klebsiella pneumoniae - Shufan Dong; Xuxia Liu; Tianyu Chen; Xiaoqin Zhou; Shengming Li; Shuilin Fu; Heng Gong (Current Microbiology, 2022)

Estimating the spatial-temporal distribution of urban street ponding levels from surveillance videos based on computer vision - Xin Hao; Heng Lyu; Ze Wang; Shengnan Fu; Chi Zhang (Water Resources Management, 2022)

Asymmetry of daily mean temperature series over China and its frontal mechanism - Heng Quan; Wenmi Chai; Zuntao Fu (International Journal of Climatology, 2022)
We analyse the European Center for Medium‐Range Weather Forecasts reanalysis temperature time series over China and find that daily mean temperature at 850 hPa pressure level warms gradually and cools rapidly, which is known as the asymmetry property. Previous studies pointed out that front events contribute to this asymmetry property, but only presented indirect evidences. Here, we confirm this conjecture with more convincing and direct evidences. The time series of front events are obtained over China by an improved objective front detection algorithm. The high Pearson correlation between time series of monthly temperature asymmetry measure and time series of monthly front events over some specific regions indicates they are closely related to each other and front events indeed contribute to temperature asymmetry. We discover that the North China Plain is a representative region where front events contribute to temperature asymmetry significantly. Further diagnostic analysis by temperature tendency equation shows that the asymmetry of daily mean temperature series is due to the asymmetry between the frequency and intensity (mainly the intensity of meridional nonlinear advection term) of cold and warm fronts in North China Plain.

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Evaluation of re-analyses over China based on the temporal asymmetry of daily temperature variability - Wenmi Chai; Yu Huang; Lichao Yang; Heng Quan; Zuntao Fu (Theoretical and Applied Climatology, 2022)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Genetic mapping reveals BjRf as a candidate gene controlling fertility restoration of the oxa CMS in Brassica juncea - Qiqi Cheng; Peijie Yao; Hui Li; Yiming Han; Kejing Xu; Shuangping Heng; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2021)

Study of pollutant accumulation characteristics and microbial community impact at three bioretention facilities - Ya-jiao Li; Heng Fu; Jing-yu Zhang; Zhao-xin Zhang; Jia-ke Li (Environmental Science and Pollution Research, 2021)

Responses of karst on sequence interfaces—a case study of Ordovician in Tarim Basin, NW China - Xuanzi Zhongliang; Heng Fu; Leli Cheng (Arabian Journal of Geosciences, 2021)

Application of an improved multifractal detrended fluctuation analysis approach for estimation of the complexity of daily precipitation - Liangliang Zhang; Heng Li; Dong Liu; Qiang Fu; Mo Li; Muhammad Abrar Faiz; Shoaib Ali; Muhammad Imran Khan; Tianxiao Li (International Journal of Climatology, 2021)
Affected by climate change and high‐intensity human activities, the precipitation series is characterized by nonlinear complex fluctuations. In order to accurately quantify the precipitation complexity, the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method was introduced to address the shortcomings of the traditional multifractal detrended fluctuation analysis (MFDFA), and the CEEMDAN‐MFFA method was proposed to explore the spatiotemporal variability and possible causes of precipitation complexity in Northeast China (NEC). The results showed that the traditional MFDFA method generally overestimated precipitation complexity. However, the CEEMDAN‐MFFA method improved the accuracy and reliability of precipitation complexity analysis. Daily precipitation series in NEC were characterized by multifractal with high uncertainty and anti‐persistence. The lowest precipitation complexity was 0.573, which appeared in Qian'an, Jilin Province, and the highest precipitation complexity was 1.108, which appeared in the Boketu, Inner Mongolia. The cities with high complexity of daily precipitation are sporadically distributed in the three provinces of Heilongjiang, Jilin and Liaoning. The average complexity is ~0.892, accounting for 22.5% of the total administrative districts. The complexity of daily precipitation showed a statistically insignificant downward trend with time. The precipitation dynamics structure in the southeast and northwest of the study area was complex, and the precipitation was less predictable than other regions. However, the precipitation dynamics structure was relatively simple and the precipitation was easily predictable in the northeastern, central and southwestern regions. Elevation, topographic relief, changes in water area, forest area and agricultural production were the main influencing factors for the differences in precipitation complexity. Results also revealed that increasing the area of forestland by means of protecting and breeding forests, via regulation of the forest ecosystems to alleviate the complex precipitation process will become a reliable approach to cope with nonstationary precipitation.

Optimal segmentation scale selection and evaluation of cultivated land objects based on high-resolution remote sensing images with spectral and texture features - Heng Lu; Chao Liu; Naiwen Li; Xiao Fu; Longguo Li (Environmental Science and Pollution Research, 2021)

Back-analysis of Donghekou landslide using improved DDA considering joint roughness degradation - Jinmei Wang; Yingbin Zhang; Yanlong Chen; Qingdong Wang; Chenlin Xiang; Haiying Fu; Pan Wang; John X. Zhao; Lian-heng Zhao (Landslides, 2021)

Fine-mapping of the BjPur gene for purple leaf color in Brassica juncea - Shuangping Heng; Qiqi Cheng; Tian Zhang; Xujia Liu; Hao Huang; Peijie Yao; Zhixin Liu; Zhengjie Wan; Tingdong Fu (Theoretical and Applied Genetics, 2020)

The antiviral protein viperin interacts with the viral N protein to inhibit proliferation of porcine epidemic diarrhea virus - Jiaqi Wu; Heng Chi; Yali Fu; Aiping Cao; Jingxuan Shi; Min Zhu; Lilin Zhang; Deping Hua; Jinhai Huang (Archives of Virology, 2020)

A new 5α,8α-epidioxysterol with immunosuppressive activity from the South China Sea soft coral Sinularia sp. - Min Yang; Lin-Fu Liang; Heng Li; Wei Tang; Yue-Wei Guo (Natural Product Research, 2020)

The Vif protein of caprine arthritis encephalitis virus inhibits interferon production - Yali Fu; Dong Lu; Yanxin Su; Heng Chi; Jiashun Wang; Jinhai Huang (Archives of Virology, 2020)

Response of individual sizes and spatial patterns of Deyeuxia angustifolia to increasing water level gradient in a freshwater wetland - Heng Ren; Fu-xi Shi; Rong Mao; Yue-dong Guo; Wen-zhi Zhao (Environmental Science and Pollution Research, 2020)

Genetic diversity in the endangered Camellia nitidissima assessed using transcriptome-based SSR markers - Xin-lei Li; Jie Wang; Zheng-qi Fan; Ji-yuan Li; Heng-fu Yin (Trees, 2020)

Source analysis and risk assessment of heavy metals in development zones: a case study in Rizhao, China - Huimin Zhuo; Xu Wang; Heng Liu; Sanze Fu; Hui Song; Lijun Ren (Environmental Geochemistry and Health, 2020)

Regulation of Pyruvate Formate Lyase-Deficient Klebsiella pneumoniae for Efficient 1,3-Propanediol Bioproduction - Wenjing Bao; Renquan Wei; Xuxia Liu; Shufan Dong; Tianyu Chen; Shuilin Fu; Heng Gong (Current Microbiology, 2020)

Soil heavy metal contamination and health risk assessment associated with development zones in Shandong, China - Huimin Zhuo; Sanze Fu; Heng Liu; Hui Song; Lijun Ren (Environmental Science and Pollution Research, 2019)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

Construction of restorer lines and molecular mapping for restorer gene of hau cytoplasmic male sterility in Brassica napus - Chao Wei; Huadong Wang; Shuangping Heng; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Jinxiong Shen; Tingdong Fu (Theoretical and Applied Genetics, 2019)

Climate Change Penalty to Ozone Air Quality: Review of Current Understandings and Knowledge Gaps - Tzung-May Fu; Heng Tian (Current Pollution Reports, 2019)

Timing and genesis of Cu–(Au) mineralization in the Khetri Copper Belt, northwestern India: constraints from in situ U–Pb ages and Sm–Nd isotopes of monazite-(Ce) - Xiao-Chun Li; Mei-Fu Zhou; A. E. Williams-Jones; Yue-Heng Yang; Jian-Feng Gao (Mineralium Deposita, 2019)

In Vivo Biocompatibility and Improved Compression Strength of Reinforced Keratin/Hydroxyapatite Scaffold - Jie Fan; Meng-Yan Yu; Tong-da Lei; Yong-Heng Wang; Fu-Yuan Cao; Xiao Qin; Yong Liu (Tissue Engineering and Regenerative Medicine, 2018)

Morphological and genetic characterization of a new cytoplasmic male sterility system (oxa CMS) in stem mustard (Brassica juncea) - Shuangping Heng; Sansan Liu; Chunxiu Xia; HongYu Tang; Fei Xie; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2018)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Numerical analysis of the flow field in a sloshing tank with a horizontal perforated plate - Heng Jin; Yong Liu; Huajun Li; Qiang Fu (Journal of Ocean University of China, 2017)

Identification of different cytoplasms based on newly developed mitotype-specific markers for marker-assisted selection breeding in Brassica napus L. - Shuangping Heng; Fengyi Chen; Chao Wei; Kaining Hu; Zonghui Yang; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Ping Si; Tingdong Fu; Jinxiong Shen (Plant Cell Reports, 2017)

Cultivated land information extraction in UAV imagery based on deep convolutional neural network and transfer learning - Heng Lu; Xiao Fu; Chao Liu; Long-guo Li; Yu-xin He; Nai-wen Li (Journal of Mountain Science, 2017)

Evolution Mechanism and Rainfall Warning Criteria for Maijianwo Slope in Henan Province, China - Yi-heng Pan; Jian-ping Chen; Li-qing Wu; Wei Wang; Fu-lin Tan (Geotechnical and Geological Engineering, 2017)

Seroprevalence and risk factors of bovine viral diarrhoea virus (BVDV) infection in yaks (Bos grunniens) in northwest China - Jian-Gang Ma; Wei Cong; Fu-Heng Zhang; Sheng-Yong Feng; Dong-Hui Zhou; Yi-Ming Wang; Xing-Quan Zhu; Hong Yin; Gui-Xue Hu (Tropical Animal Health and Production, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Fine mapping and candidate gene analysis of an anthocyanin-rich gene, BnaA.PL1, conferring purple leaves in Brassica napus L. - Haibo Li; Lixia Zhu; Gaigai Yuan; Shuangping Heng; Bin Yi; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu; Jing Wen (Molecular Genetics and Genomics, 2016)

Piromelatine ameliorates memory deficits associated with chronic mild stress-induced anhedonia in rats - Wan Fu; Heng Xie; Moshe Laudon; Shouhong Zhou; Shaowen Tian; Yong You (Psychopharmacology, 2016)

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

Characterization and classification of one new cytoplasmic male sterility (CMS) line based on morphological, cytological and molecular markers in non-heading Chinese cabbage (Brassica rapa L.) - Shuangping Heng; Dianyi Shi; Zhenhua Hu; Tao Huang; Jinping Li; Liyan Liu; Chunxiu Xia; Zhenzhen Yuan; Yuejin Xu; Tingdong Fu; Zhengjie Wan (Plant Cell Reports, 2015)

Improvement of 1,3-propanediol production in Klebsiella pneumoniae by moderate expression of puuC (encoding an aldehyde dehydrogenase) - Chengqian Zhu; Xiao Jiang; Yongqiang Zhang; Jie Lin; Shuilin Fu; Heng Gong (Biotechnology Letters, 2015)

Clinical effect of postconditioning in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention: a meta-analysis of randomized controlled trials - Xian-qing Hu; Jian Cheng; Biao Tang; Zhong-heng Zhang; Ke Huang; Yi-ping Yang; Yan-yan Mao; Ming Zhong; Shen-wen Fu (Journal of Zhejiang University-SCIENCE B, 2015)

The genetic basis of population fecundity prediction across multiple field populations of Nilaparvata lugens - Zhong Xiang Sun; Yi Fan Zhai; Jian Qing Zhang; Kui Kang; Jing Heng Cai; Yonggui Fu; Jie Qi Qiu; Jia Wei Shen; Wen Qing Zhang (Molecular Ecology, 2015)
Identifying the molecular markers for complex quantitative traits in natural populations promises to provide novel insight into genetic mechanisms of adaptation and to aid in forecasting population dynamics. In this study, we investigated single nucleotide polymorphisms ( SNP s) using candidate gene approach from high‐ and low‐fecundity populations of the brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) divergently selected for fecundity. We also tested whether the population fecundity can be predicted by a few SNP s. Seven genes ( ACE , fizzy, HMGCR , LpR, Sxl, Vg and VgR ) were inspected for SNP s in N. lugens , which is a serious insect pest of rice. By direct sequencing of the complementary DNA and promoter sequences of these candidate genes, 1033 SNP s were discovered within high‐ and low‐fecundity BPH populations. A panel of 121 candidate SNP s were selected and genotyped in 215 individuals from 2 laboratory populations ( HFP and LFP ) and 3 field populations ( GZP , SGP and ZSP ). Prior to association tests, population structure and linkage disequilibrium ( LD ) among the 3 field populations were analysed. The association results showed that 7 SNP s were significantly associated with population fecundity in BPH . These significant SNP s were used for constructing general liner models with stepwise regression. The best predictive model was composed of 2 SNP s ( ACE ‐862 and VgR ‐816 ) with very good fitting degree. We found that 29% of the phenotypic variation in fecundity could be accounted for by only two markers. Using two laboratory populations and a complete independent field population, the predictive accuracy was 84.35–92.39%. The predictive model provides an efficient molecular method to predict BPH fecundity of field populations and provides novel insights for insect population management.

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Emodin elicits cytotoxicity in human lung adenocarcinoma A549 cells through inducing apoptosis - Wing-Yan Li; Yam-Fung Ng; Huan Zhang; Zi-Dong Guo; De-Jian Guo; Yiu-Wa Kwan; George Pak-Heng Leung; Simon Ming-Yuen Lee; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2014)

Functional analyses of a flavonol synthase–like gene from Camellia nitidissima reveal its roles in flavonoid metabolism during floral pigmentation - Xing-Wen Zhou; Zheng-Qi Fan; Yue Chen; Yu-Lin Zhu; Ji-Yuan Li; Heng-Fu Yin (Journal of Biosciences, 2013)

Acceleration effect of amino acid supplementation on glycerol assimilation by Escherichia coli in minimal medium - Gang Xiang; Jiang Li; JiFu Duan; Fei Shao; Jiajie Xu; Shuilin Fu; Heng Gong (Biotechnology Letters, 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Ischemia hypothermia improved contractility under normothermia reperfusion in the model of cultured cardiomyocyte - Heng Li; Xiangshao Fang; Zhengfei Yang; Yue Fu; Yu Wang; Jinlang Wu; Tao Yu; Zitong Huang (In Vitro Cellular & Developmental Biology - Animal, 2012)

Na+/H+ Exchanger 1 Gene Expression in Tissues of Yellow Chicken - Zhang-yong Ning; Yu-fu An; Wen-bao Qi; Heng Wang; Jia-qiang Pan; Xin-tao Wu; Ming Liao (Biochemical Genetics, 2012)

Breakdown of orthopyroxene contributing to melt pockets in mantle peridotite xenoliths from the Western Qinling, central China: constraints from in situ LA-ICP-MS mineral analyses - Ben-Xun Su; Hong-Fu Zhang; Yue-Heng Yang; Patrick Asamoah Sakyi; Ji-Feng Ying; Yan-Jie Tang (Mineralogy and Petrology, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Influence of P-glycoprotein on embryotoxicity of the antifouling biocides to sea urchin (Strongylocentrotus intermedius) - Xue Xu; Jingxuan Fu; Heng Wang; Baidong Zhang; Xia Wang; Yonghua Wang (Ecotoxicology, 2011)

Important Role of Catalase in the Production of β-carotene by Recombinant Saccharomyces cerevisiae under H2O2 Stress - Guo-liang Yan; Heng-yu Liang; Zhi-qun Wang; Xiao-fan Yang; Dan Liu; Jin-fu Liu; Chang-qing Duan (Current Microbiology, 2011)

The origin of spongy texture in minerals of mantle xenoliths from the Western Qinling, central China - Ben-Xun Su; Hong-Fu Zhang; Patrick Asamoah Sakyi; Yue-Heng Yang; Ji-Feng Ying; Yan-Jie Tang; Ke-Zhang Qin; Yan Xiao; Xin-Miao Zhao; Qian Mao; Yu-Guang Ma (Contributions to Mineralogy and Petrology, 2011)

Recurrent Cerebellar Hemorrhage: Case Report and Review of the Literature - Yung-Tsan Wu; Ming-Fu Hsieh; Heng-Yi Chu; Shao-Chi Lu; Shin-Tsu Chang; Tsung-Ying Li (The Cerebellum, 2010)

NP-184[2-(5-methyl-2-furyl) benzimidazole], a novel orally active antithrombotic agent with dual antiplatelet and anticoagulant activities - Heng-Lan Kuo; Jin-Cherng Lien; Ching-Hu Chung; Chien-Hsin Chang; Shyh-Chyi Lo; I-Chun Tsai; Hui-Chin Peng; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat - Tian-Heng Ren; Zu-Jun Yang; Ben-Ju Yan; Huai-Qiong Zhang; Shu-Lan Fu; Zheng-Long Ren (Euphytica, 2009)

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)

Importance of Small Pores in Microcrystalline Cellulose for Controlling Water Distribution during Extrusion–Spheronization - Josephine L. P. Soh; Lei Yang; Celine V. Liew; Fu D. Cui; Paul W. S. Heng (AAPS PharmSciTech, 2008)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Increased protein and mRNA expression of endostatin in the ischemic brain tissue of rabbits after middle cerebral artery occlusion - Heng-Li Tian; Hao Chen; Yu-Hui Cui; Tao Xu; Liang-Fu Zhou (Neuroscience Bulletin, 2007)

Tracing magma mixing in granite genesis: in situ U–Pb dating and Hf-isotope analysis of zircons - Jin-Hui Yang; Fu-Yuan Wu; Simon A. Wilde; Lie-Wen Xie; Yue-Heng Yang; Xiao-Ming Liu (Contributions to Mineralogy and Petrology, 2006)

Local Base Order Influences the Origin of ccr5 Deletions Mediated by DNA Slip Replication - Chi-Yu Zhang; Ji-Fu Wei; Shao-Heng He (Biochemical Genetics, 2005)